Good Faith in Life Insurance Contract by Indonesian Court - Huda, Mokhamad Khoirul (Hasanuddin University, 2017)
This paper reviews both the interpretation of good faith and its implementation by the Court in terms of life insurance contracts. The principle of good faith in life insurance contracts was under the provision of the Article 251 Wet Boek van Kophandel which assigned the obligation of good faith on the insured. Based on the context of its historical and systematical interpretation, the obligation of good faith should be on both sides, the insurer and the insured. The insured had an obligation to inform any material facts and the insurer had to investigate those all facts. Until recent days, however, judges in all levels of Court did not have any shared and full understanding on the interpretation of good faith in life insurance contracts. As the result, many Courts were frequently inconsistent with each other. Hence, the sense of fairness the people perceived from the court verdict was not achieved.